DEVELOPMENT POLICY INNOVATION IN INDONESIA: THE APPLICATION OF SMART RURAL FOR THE DEVELOPMENT OF TOURIST VILLAGES - Dian Kagungan; Feni Rosalia (JWP (Jurnal Wacana Politik), 2022)
The study of village development is currently popular in political and government discourse in Indonesia. The innovative steps in village development in Indonesia is the application of the smart rural concept. Smart rural is defined as a rural area that is built sustainably with a potential specialization approach, the use of technology, and a bottom-up planning process to improve the regional economy. Therefore, this study will try to look at the development of smart rural areas in Indonesia with focus on developing smart rural-based villages and tourism, precisely in Hanura Village, and Harapan Jaya Village, Pesawaran Regency. The research was conducted by conducting observations, interviews, and documentation. The results of this study are: the Innovation Program for the Prosperous Village Movement (GaDIS) in Jarapan Jaya Village has the aim of creating a strong and independent village in the business unit under the Village Owned Enterprise (BUMDes) that utilizes the local potential of the village (tourism), the use of technology, and the GaDIS Program to encourage community empowerment which leads to increased community welfare. The commitment of BUMDes managers, tourism awareness groups and economic actors is carried out appropriately based on the business plan of the program’s final destination. Meanwhile, Hanura Village has utilized information technology into its government (smart government). participating communities (smart community), utilizing the environment (smart environment) Synergy in the implementation of smart rural-based development is good, the pattern of good communication relationships, feedback, trust and creativity since planning process to the implementation of the smart rural program.